Capital Punishment and the Criminal Corpse in Scotland, 1740–1834 2017
DOI: 10.1007/978-3-319-62018-3_5
|View full text |Cite
|
Sign up to set email alerts
|

The Spectacle of the Scaffold

Abstract: The focus of Part I of this volume was to gain an understanding of the implementation of the death sentence in Scotland. It provided an exploration of the contextual and judicial drivers that impacted upon its use and quantitative analyses of focal periods to enhance our knowledge of Scotland's capital punishment history between 1740 and 1834. Part II will now turn to present a qualitative exploration of public executions in Scotland and an investigation into the changing nature of capital punishment and execu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The reason for this likely lies in the fact that Kilday found that around half of the women were also indicted as 'resetters', who would pass on the stolen goods, and in three quarters of the total cases they were also charged with assault. 69 Therefore, it is probable that most of these women were convicted of either assault or reset of theft which were lesser crimes than robbery itself and did not carry a capital punishment.…”
Section: Property Offencesmentioning
confidence: 99%
“…The reason for this likely lies in the fact that Kilday found that around half of the women were also indicted as 'resetters', who would pass on the stolen goods, and in three quarters of the total cases they were also charged with assault. 69 Therefore, it is probable that most of these women were convicted of either assault or reset of theft which were lesser crimes than robbery itself and did not carry a capital punishment.…”
Section: Property Offencesmentioning
confidence: 99%